2022
DOI: 10.30699/fhi.v11i1.373
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Virtual Reality on Reducing the Anxiety in Children: A Systematic Review

Abstract: Introduction: Many children may experience anxiety in treatment settings, especially in situations such as before surgery, dentistry and radiology. Virtual reality technology can provide a platform for reducing children's anxiety by creating a sense of presence in an unreal world. The aim of this study was to investigate the effect of virtual reality technology on reducing anxiety in children.Materials and Methods: A systematic review of randomized clinical trial studies was conducted in English without any ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“… 4 There are countless reasons why implementing eHealth systems is still challenging despite the available studies on clinical benefits, efficacy costs, and increased access to healthcare services at the macrolevel. 5 , 6 , 7 Regardless of the potential advantages and technical superiority of telemedicine, its admission is often known as a failed project, 8 and the user's nonacceptance is one of the significant reasons for its failure. 9 Put differently, the success of every new technology depends on numerous factors, including specialists' knowledge and perceptions of the concept, acquired attitude skills, and work environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 There are countless reasons why implementing eHealth systems is still challenging despite the available studies on clinical benefits, efficacy costs, and increased access to healthcare services at the macrolevel. 5 , 6 , 7 Regardless of the potential advantages and technical superiority of telemedicine, its admission is often known as a failed project, 8 and the user's nonacceptance is one of the significant reasons for its failure. 9 Put differently, the success of every new technology depends on numerous factors, including specialists' knowledge and perceptions of the concept, acquired attitude skills, and work environments.…”
Section: Introductionmentioning
confidence: 99%
“…The health domain has experienced a slower trend than other sectors in employing ICT 4 . There are countless reasons why implementing eHealth systems is still challenging despite the available studies on clinical benefits, efficacy costs, and increased access to healthcare services at the macrolevel 5–7 . Regardless of the potential advantages and technical superiority of telemedicine, its admission is often known as a failed project, 8 and the user's nonacceptance is one of the significant reasons for its failure 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, to facilitate decision‐making and reduce avoidable hospital admissions and extended antibiotic usage, highly accurate clinical decision support systems (CDSS) are required. The use of digital technologies is not a new issue in the management of diseases today 15–23 . Over the past six decades, artificial intelligence (AI) has been widely used in many areas of medical research and clinical practice 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of digital technologies is not a new issue in the management of diseases today. [15][16][17][18][19][20][21][22][23] Over the past six decades, artificial intelligence (AI) has been widely used in many areas of medical research and clinical practice. 24,25 These days, AI methods like artificial neural networks (ANN) are being used by healthcare organizations to enhance data analysis, clinical diagnosis, cancer and other illness prediction, image analysis and interpretation, medication creation, and patient care.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Telerehabilitation provides rehabilitation services using various technologies, including virtual reality, mobile phone applications, artificial intelligence, iPad, mobile games, online video conferencing, and others. [ 9 10 11 12 13 14 ] Previous studies have shown that telerehabilitation is effective, safe, and feasible in patients with chronic obstructive pulmonary disease,[ 15 ] patients with coronavirus disease 2019 (COVID-19),[ 16 ] and patients undergoing chemotherapy. [ 17 ] Also, Baigi et al .…”
Section: Introductionmentioning
confidence: 99%